Characterization and QTL Mapping of a Major Field Resistance Locus for Bacterial Blight in Rice - Jae-Ryoung Park; Chang-Min Lee; Hyeonso Ji; Man-Kee Baek; Jeonghwan Seo; O-Young Jeong; Hyun-Su Park (Plants, 2022)
Bacterial blight (BB) disease, caused by Xanthomonas oryzae pv. oryzae (Xoo), is among the major factors that can cause rice yields to decrease. To address BB disease, researchers have been looking for ways to change pesticides and cultivation methods, but developing resistant cultivars is the most effective method. However, the resistance and genetic factors of cultivars may be destroyed due to the emergence of new Xoo species caused by recent and rapid climate changes. Therefore, breeders need to identify resistance genes that can be sustained during unpredictable climate changes and utilized for breeding. Here, qBBR11, a quantitative trait locus (QTL) for resistance to BB disease, was detected in KJ (Korea Japonica varieties) 11_067 to KJ11_068 on chromosome 11 in a population derived by crossing JJ (Jeonju) 623 and HR(High resistant)27,195, which possess similar genetic backgrounds but different degrees of resistance to BB disease. qBBR11 was reduced from 18.49–18.69 Mbp of chromosome 11 to 200 kbp segment franked. In this region, 16 candidate genes were detected, and we identified 24 moderate-impact variations and four high-impact variations. In particular, high-impact variations were detected in Os11g0517800 which encode the domain region of GCN2 which is the eIF-2-alpha kinase associated with the resistance of abiotic/biotic stress in rice. In JJ623, which is moderately resistant to BB disease, a stop codon was created due to single nucleotide polymorphism (SNP). Therefore, compared with HR27195, JJ623 has weaker resistance to BB disease, though the two have similar genetic backgrounds. The results suggest that variation in the qBBR11 region regulates an important role in improving resistance to BB diseases, and qBBR11 is useful in providing an important resource for marker-assisted selection to improve mechanisms of resistance to BB disease.